Iron homeostasis as a cell detoxification mechanism in Mesorhizobium qingshengii J19 under yttrium exposure - Coimbra, Carina; Morais, Paula V.; Branco, Rita (Frontiers in Microbiology, 2024)
Yttrium (Y), an important rare earth element (REE), is increasingly prevalent in the environment due to industrial activities, raising concerns about its toxicity. Understanding the effects of Y on microorganisms is essential for bioremediation and biorecovery processes. This study investigates how Mesorhizobium qingshengii J19, a strain with notable resistance to Y, manages iron homeostasis as a detoxifying mechanism under Y stress. Using comparative genomic and transcriptomic analyses, we explored the gene expression profile of strain J19 to identify the mechanisms underlying its high Y resistance and effective Y removal from the medium. Genome-wide transcriptional profiling revealed 127 significantly differentially expressed genes out of 6,343 under Y stress, with 36.2 % up-regulated and 63.8 % down-regulated. Notably, Y exposure significantly affects cellular iron homeostasis and activates arsenic detoxifying mechanisms. A key finding was the 7.6-fold up-regulation of a TonB transporter gene, indicating its crucial role in Y detoxification. Real-time PCR (RT-PCR) analysis of the selected gene confirmed the accuracy of RNA sequencing results. Further validation showed that iron supplementation mitigates Y-induced growth inhibition, leading to reduced ROS production in strain J19. This study elucidates the molecular mechanisms by which strain M. qingshengii J19 adapts to Y stress, emphasizing the importance of iron in controlling ROS and protecting against Y toxicity. It also highlights critical pathways and adaptive responses involved in the strain's resilience to metal stress.